A case of primary orbital liposarcoma with dedifferentiated transformation from a well-differentiated form - Mika Tanabe; Hiroshi Yoshikawa; Masatoshi Fukushima; Masahiro Mizoguchi; Masato Akiyama; Yuhei Sangatsuda; Fumiya Narutomi; Koh-Hei Sonoda (American Journal of Ophthalmology Case Reports, 2024)
Purpose: Primary orbital liposarcomas are rare. To the best of our knowledge, only four cases of primary dedifferentiated liposarcomas of the orbit have been reported. Furthermore, there have been no reports of primary orbital liposarcomas transitioning from a highly differentiated to a dedifferentiated form. Here, we report a case of primary orbital liposarcoma that was well-differentiated at the time of initial resection at our hospital but had dedifferentiated on recurrence 10 years after the initial resection. Observations: The patient was diagnosed with an inflammatory mass after an initial tumor resection by a previous physician at age 52. Thereafter, there were four recurrences (first to fourth recurrences), and the patient underwent five surgeries and radiotherapy. For the fifth recurrence, he first visited our hospital at age 64 and was diagnosed with a well-differentiated liposarcoma after undergoing tumor resection. When the tumor recurred 9 years later (the sixth recurrence), it was well-differentiated. When the tumor recurred (the seventh recurrence) six months after surgery at the age of 73 years, the patient underwent orbital exenteration because of rapid tumor growth, and pathological examination showed that the tissue had changed to a dedifferentiated liposarcoma. Conclusions and Importance: Primary well-differentiated orbital liposarcoma may transform to a dedifferentiated form over time. The risk of dedifferentiation at recurrence should be considered in developing a treatment plan, even if the initial pathology is a well-differentiated liposarcoma.